Understanding land warfare - Tuck, Christopher (London : Routledge, Taylor & Francis Group, 2014)
'This textbook provides a thorough grounding in the vocabulary, concepts, issues and debates associated with modern land warfare'--
Includes bibliographical references and index.
Keywords: Military art and science; Military art and science -- Case studies; HISTORY / Military / Strategy; HISTORY / Military / General; POLITICAL SCIENCE / Political Freedom & Security / General